Role of Foreign Portfolio Investment in Dynamism of Indian Capital Market: A Causality Study - Ms. Meenakshi Sharma; Mr. Anil Kumar Mittal (Ramanujan International Journal of Business and Research, 2019)
The flow of foreign capital in the form of institutional investment assumed a greater significance in the growth and development of the developing nations. The era of globalization has converted the whole world into a single form of market where there is the unrestricted flow of funds takes place from one country to another country. The same influence also observed in the Indian economy. When the reform process provided a platform to the foreign institutions to make an investment in the national boundary by lifting the different barriers and offering them liberty in the investment policies. Taking into consideration such a role of foreign funds in the Indian market present paper explored the trend of foreign portfolio investment in concern of the Indian capital market. The present paper also investigates the Causal Relationship between Foreign Portfolio Investment and Indian Stock market NSE index Nifty Return. In this context, different variables associated with portfolio investment such as FPIP, FPIS, FPIN, Ratio FPIP, Ratio FPIS, Ratio FPIN have been taken. NSE Nifty has been taken as the benchmark for the Indian stock market. Monthly data from April 2010 to March 2019 have been taken as the sample. To test the causality for the time series data Granger Causality test has been applied. The result of the study showed that there is no causality between FPIS and NSE Return and the same result is reported for Ratio FPIN and NSE Returns during the study period. Result also revealed the evidence for bi-directional causality between Ratio of FPIP and Returns, Unidirectional Causality found to exist when causality test is applied on the Ratio of FPIS, FPIP, FPIN, and NSE Returns for the period under study.